Y - Generation and Its Supply Chain Strategy for Housing Affordability: An Evidence From Indonesia - Aswin Rahadi, Raden; Putri Pradana, Dian; Nita, Arfenia; Lazuardi Kitri, Mandra; Anny Nainggolan, Yunieta; Rahmatsyah Putranto, Nur Arief; Muhammad, Zikri (ExcelingTech, 2020)
Y - Generation of Indonesian has a lack of affordability in purchasing a house. It has become a much-discussed issue and attracted the researchers attention, both in terms of preferences, indexes, and solutions to deal with the problem. Generation Ys preferences in purchasing a house were also investigated in this research to understand which preferences will affect the demand and price of the houses because price is also an indicator used to identify the affordability. In addition, those preferences also will help some parties involved in housing transactions to create a strategy that will increase the affordability index. The data in this research is gathered using mixed methods in which the qualitative is used in the 5 interviews with the property experts to gain the questionnaire items, and the questionnaire as the quantitative method with 206 respondents limited to Generation Y who have fixed income every month and are willing to have a house in Jakarta. The data then further processed using PLS-SEM analysis. This research finally found that Generation Ys preferences are divided into four categories which are product specifications, future considerations, supplemental factors, and dweller characteristics (stated in sequence from the most influential to the least influential). In terms of affordability, according to five banks with lowest interest rate, BTN as well BRI and Mandiri have become the most affordable bank for Generation Y to do KPR because the indexes were 4.41% (can afford) and 95.59% (cannot afford) or the highest compared to BJB and BCA.